INTRODUCTION OF SPORTS ORIENTEERING INTO THE EDUCATIONAL PROCESS OF SECONDARY SCHOOLS - GRYNIUK, Oleg; GULYAS, Tanya; RADCHENKO, Ariana (Bulletin of Taras Shevchenko National University of Kyiv, Geography, 2025)
Background. Orienteering is one of the popular sports that contributes to the development of physical, intellectual, and psycho-emotional skills. Due to its unique combination of physical activity and the need for quick decision-making, this sport becomes an important element in the upbringing of the younger generation. In the modern educational process, orienteering has great potential for integration into curricula, as it not only promotes physical development but also cultivates critical thinking skills, teamwork, and adaptability to various conditions. However, there are certain difficulties and challenges that need to be overcome to achieve optimal results. Therefore, it is relevant to identify ways to implement orienteering into the educational process. The aim of this study is to determine effective ways of integrating orienteering into the educational process to popularize this sport and develop students’ physical, intellectual, and psycho-emotional skills. Methods. The study analyzed foreign experience and orienteering programs with the potential for integration into the educational process, reviewed existing programs and scientific research on orienteering in Ukraine, and identified a competency based approach. Results. Orienteering has a significant impact on the development of students’ physical and intellectual skills. One of the key challenges in integrating orienteering into the educational process is the need to adapt curricula and train teaching staff. The recommendations proposed in the study demonstrate that with proper implementation, orienteering can become an important element of the educational process, contributing not only to physical education but also to the development of key competencies, critical thinking, leadership qualities, and enhancing students’ overall motivation for learning. Conclusions. The experience of many countries shows that incorporating orienteering into educational programs has a positive impact on the development of students and promotes their overall harmonious growth. The conducted research highlights the significant potential of orienteering as an effective means of developing students’ physical, intellectual, and psycho-emotional skills. Integrating this sport into the educational process contributes not only to the physical development of young people but also to the formation of essential life competencies, such as critical thinking, teamwork, and adaptability to changing conditions. At the same time, the challenges associated with implementing orienteering can be overcome by developing an adapted teaching methodology and integrating this sport into curricula, particularly in geography.